The Taptana Cañari: an ancestral way of thinking for the development of human qualities in teacher training - Troya Vásquez, Rosa Ildaura (2025)
This article analyzes the impact of Taptana Cañari thought on the development of human qualities for life in teachers, showing how this ancient way of thinking, when combined with current teaching methods, fosters the growth of social, communication, and moral skills in teaching. This study used a qualitative approach through data collection instruments such as interviews, video, field diaries, and questionnaires, administered to a sample of 25 teachers. Content analysis software such as MAXQDA and NVivo were used to analyze the data. Among the results, it is noteworthy that the application of this method helped improve virtues such as feeling part of a group, respect for different ways of being, attentive listening, and teamwork, promoting a significant change in the relationships between teachers and students and in the way they understand teaching. The findings support the idea that humanistic and constructivist teaching with a human-centered education, with an emphasis on culture and peaceful coexistence, not only improves teaching but also promotes the personal and professional growth of the individual, contributing to the achievement of quality and justice in education.